The impact of stock liquidity on corporate environmental information disclosure: Does climate risk matter? - Jinyu Chen; Junqi Liu; Meng He (Quantitative Finance and Economics)
From the perspective of the Chinese market microstructure, we took Chinese A-share listed companies as samples to explore the impact and mechanism of stock liquidity on the quality of corporate environmental information disclosure (EID). Our results indicated that stock liquidity has a positive impact on the quality of corporate EID. Using the stock market interconnection events of the 2014 Shanghai-Hong Kong Stock Connect and the 2016 Shenzhen-Hong Kong Stock Connect as a quasi-natural experiment and applying the Ⅳ approach, the research results remained robust after controlling for endogeneity issues. Moreover, both climate physical risk and climate transition risk positively regulated the relationship between stock liquidity and the quality of corporate EID. Further analysis revealed that the positive impact of stock liquidity on the quality of corporate EID is determined by the information effect path and governance effect path of stock liquidity, and the role of the information effect path is more important. In summary, stock liquidity has had an important feedback effect on Chinese companies' active EID behavior through two pathways: Information effect and governance effect.